2010
DOI: 10.1002/jbmr.108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting gastric acid production does not affect intestinal calcium absorption in young, healthy individuals: A randomized, crossover, controlled clinical trial

Abstract: Proton pump inhibitors (PPIs) are the most potent gastric acid suppressing drugs available, and their use is widespread. An emerging concern about chronic PPI therapy is whether these drugs impair intestinal calcium absorption, resulting in a negative calcium balance and thereby potentially causing bone loss. The objective of this study was to evaluate the acute effect of the PPI esomeprazole or placebo on intestinal calcium absorption in healthy adults. Twelve young adults participated in a placebo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 27 publications
0
51
0
5
Order By: Relevance
“…However, the only studies that have demonstrated decreased calcium absorption among PPI users have been those that specifically assessed absorption of supplemental calcium carbonate in fasting individuals (26,27). In all other scenarios using different formulations of supplemental calcium or calcium ingestion associated with meals, no effects of PPIs on calcium absorption have been shown (33)(34)(35). It remains possible, nevertheless, that very marginal decrements in net calcium absorption may, over long periods of time, induce a large enough net calcium loss to cause clinically meaningful reductions in BMD (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the only studies that have demonstrated decreased calcium absorption among PPI users have been those that specifically assessed absorption of supplemental calcium carbonate in fasting individuals (26,27). In all other scenarios using different formulations of supplemental calcium or calcium ingestion associated with meals, no effects of PPIs on calcium absorption have been shown (33)(34)(35). It remains possible, nevertheless, that very marginal decrements in net calcium absorption may, over long periods of time, induce a large enough net calcium loss to cause clinically meaningful reductions in BMD (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our inability to assess vitamin D status and nutritional intake of magnesium and calcium limits the conclusion that detrimental effect on serum calcium levels is definitely attributed to PPIs. Ca carbonate consumed under fasting condition a decade ago, two other studies assessed calcium absorption using dual-stable calcium isotopes and found no changes in fractional calcium absorption, thus concluding no effect of PPI on calcium absorption and metabolism (26,27). Similarly, a recent study of Sharara et al (28) concluded no measurable effect of PPI intake on calcium metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that PPI-users were more likely to subsequently be prescribed osteoporosis medication than non-users and that increased duration of therapy was associated with higher risks of osteoporosis medication prescription [1]. Three studies examining the effect of PPI use on calcium uptake used the dual isotope test (golden standard for intestinal calcium absorption) and these showed no evidence for decreased calcium absorption among PPI users [17][18][19].…”
Section: Introductionmentioning
confidence: 99%